iPSC-derived neural precursor cells: potential for cell transplantation therapy in spinal cord injury - Nagoshi, Narihito; Okano, Hideyuki (Cellular and molecular life sciences : CMLS, 2018)
A number of studies have demonstrated that transplantation of neural precursor cells (NPCs) promotes functional recovery after spinal cord injury (SCI). However, the NPCs had been mostly harvested from embryonic stem cells or fetal tissue, raising the ethical concern. Yamanaka and his colleagues established induced pluripotent stem cells (iPSCs) which could be generated from somatic cells, and this innovative development has made rapid progression in the field of SCI regeneration. We and other groups succeeded in producing NPCs from iPSCs, and demonstrated beneficial effects after transplantation for animal models of SCI. In particular, efficacy of human iPSC–NPCs in non-human primate SCI models fostered momentum of clinical application for SCI patients. At the same time, however, artificial induction methods in iPSC technology created alternative issues including genetic and epigenetic abnormalities, and tumorigenicity after transplantation. To overcome these problems, it is critically important to select origins of somatic cells, use integration-free system during transfection of reprogramming factors, and thoroughly investigate the characteristics of iPSC–NPCs with respect to quality management. Moreover, since most of the previous studies have focused on subacute phase of SCI, establishment of effective NPC transplantation should be evaluated for chronic phase hereafter. Our group is currently preparing clinical-grade human iPSC–NPCs, and will move forward toward clinical study for subacute SCI patients soon in the near future.